Using money market rates to assess the alternatives of fixed vs. variable rate tenders: the lesson from 1989-1998 data for Germany - Michele Manna (European Central Bank (ECB), 2002)
This paper uses the variability of money market rates to compare the conduct of the central bank's key market operation as a fixed-rate tender (FRT) or a variable-rate tender (VRT). Nowadays, leading central banks generally use FRTs or other approaches (e.g. target rates) which yield step changes in the policy rate, as opposed to the more piecemeal, but also more noisy changes resulting from the VRT rate. Given the central bankers' preference for stable money market conditions, FRTs should thus remain associated with lower market variability. In fact, daily data for the German overnight and three-month rates from 1989 to 1998, when the Bundesbank alternated FRTs and VRTs, indicate that the average variability of money market rates is broadly the same under the two tender procedures. A small model shows that this finding holds true under rather general conditions, and is not only a feature of the experience in Germany.
Keywords: E4; E5; G2; N2; 330